Therapeutic hypothermia in newborns with hypoxic-ischemic encephalopathy: An analysis of early childhood (Research, Society and Development, 2023)
Objective: To carry out a critical analysis of the results of the use of therapeutic hypothermia (HT) in newborns (NBs) affected with hypoxic-ischemic encephalopathy (HIE), with emphasis on mortality and neurodevelopment outcomes during early childhood. Methodology: This is a systematic review carried out through searches in the indexed platforms: PubMed, Lilacs, Cochrane and BVS, using the descriptors in English: “effects”, “hypoxic-ischemic encephalopathy” and “induced hypothermia”, separated by the Boolean operator (AND). Complete clinical trial articles were included, in Portuguese or English, published between 2012 and 2022, whose target population consisted of NBs, of both sexes, diagnosed with neonatal hypoxia or HIE, who underwent treatment with TH. Furthermore, only articles that emphasized mortality and neurodevelopmental outcomes from discharge to early childhood were selected. Results: The present study had a final sample of 4 articles. Through the analysis of the selected studies, it was noticed that TH acts through neuroprotection mechanisms, favoring the inhibition of the inflammatory cascade induced during the development process of HIE, helping to reduce brain injury and consequently decreasing the rates of morbidity and mortality of patients affected with HIE, contributing to the full development of children. Conclusion: The neuroprotective effect of TH is capable of reducing the presence of neurological sequelae and decreasing mortality rates in the pediatric/neonatal population affected by HIE.